Electric pulse cleaning of cornices - V. A. Zakharenko; V. V. Zakharenko; M. Yu. Nikolaev; A. G. Shkayev (Омский научный вестник)
Results of development of automatic devices for removal of ice and ice from eaves of buildings and constructions in which the technology of electroimpulsive transformations of electric energy in impulse mechanical force is realized are presented. In one of the variants, it is proposed to use a solar battery as a source of electric energy, while the presented circuit solutions ensure the autonomy of its operation in automatic mode. The results of field tests of the device confirmed the effectiveness its work are presented.